Antibacterial Test of Fruit Peel Ecoenzyme Against Staphylococcus epidermidisATCC-12228 - Anisya, Shinta; Satitiningrum, Yuni; Utami, Diana (ORGANISMS: JOURNAL OF BIOSCIENCES, 2025)
Acne vulgaris is an inflammatory skin disorder commonly caused by Staphylococcus epidermidis. Many anti-acne products on the market contain chemicals that have side effects for the user, so natural antibacterials are needed in the treatment of acne which have a smaller risk of side effects, namely by using fruit skins as ecoenzymes. This study aims to examine the effect of the concentration of ecoenzymes made from fruit peels on the inhibitory power of Staphylococcus epidermidis and knowing the optimal concentration of ecoenzymes in inhibiting the growth of Staphylococcus epidermidis bacteria. This research uses a quantitative approach with a Completely Randomized Design experimental research type. The antibacterial test used the well diffusion method with 3 different concentrations, namely 25%, 50% and 75%, the positive control used clindamycin and the negative control was sterile distilled water. The antibacterial test was conducted with three replicates for each concentration. ANOVA showed significant differences (p < 0.05). The results showed that the concentration of ecoenzymes had an effect on inhibiting the growth of Staphylococcus epidermidis. The most optimal concentration in inhibiting the growth of Staphylococcus epidermidis is ecoenzyme with a concentration of 75% with an average inhibitory zone diameter of 10.2 mm (strong category).